Riboflavin ameliorates the L-NAME induced brain injury - F., Camille; Nunes, Julio C.; Zandoná, Mariana S.; Bessa-Guerra, Thais de R.; Perret, Caio; A. Fiorelli, Stenio Karlos; R. Almeida, Camila; Fiorelli, Rossano K. A.; Karlos, Stenio; Nascimento, Jacqueline F. do; Castro, Renata R.T.; Gonçalves, Thiago R.; et al. (International Journal of Advanced Engineering Research and Science, 2020)
Introduction: Oxidative stress has been associated with the pathogenesis of vascular disorders as hypertension and stroke. Studies have been carried out to identify preventive alternative therapies, including vitamins with antioxidant power. Methods: Twenty-four adult male rats (SHR-sp) were subdivided into four groups with six rats (n=6) each: control (not treated), riboflavin (B2 treated), B2 plus L-NAME, and L-NAME. Individual neurologic outcome status was appraised through maze, balance and motor tests. Oxidative stress serum markers (Homocysteine and Malonic Dialdehyde) were determined for each group. The hypotensive effect (p< 0.05) observed with L-NAME: 196.5 ± 1.97mmHg (L-NAME plus B2), 195 ± 3.3mmHg (B2); 235.3 ± 2.16mmHg (control), 233.7 ± 4.50 mmHg (L-NAME). There was neuroprotective effect of riboflavin in the response to those neurological tests. Regarding oxidative stress markers, animals treated with riboflavin showed lower values (p<0.05), suggesting better protection. Conclusions: Even under NO synthase inhibition, riboflavin enhanced neurological outcome status and reduced systolic pressure levels. Discoveries suggest riboflavin might become a preventive and regenerative strategy of stroke management.